Impact of Digitalization on Service Marketing in the Indian Banking Industry - Sharma, Pooja; Gupta, Dr. Sudipta Sen (Gyan Management Journal, 2023)
Globally, Indian banking is making the move to digitization. By the late 1980s, the Indian banking industry had realized the need for digitalization and that customer service needed to be considered as an important aspect . Due to the adverse effects of several financial reforms on India in the late 1980s, the banking industry saw a need to improve customer service and computerize the recording of transactions and knowledge accounting. Today, all banks make significant investments in digital projects to keep a competitive advantage and offer their clients the best service possible. After its launch, customers have greatly profited from the convenience and time savings. All manual processes and activities have been replaced by digital services. Although it has benefited customers and had a significant impact on the Indian banking sector, there are still a number of difficulties that arise. This paper will examine the effects of digitalization on service marketing in the Indian banking sector and how it has changed over time. This study’s main goal is to measure how satisfied bank customers are with the online services they receive from banks . This study makes use of the e – Servqual method to measure quality of services provided to banking customers after digitalization has taken place in the banking customers.